Agricultural extension and technology adoption for food security: Evidence from Uganda - Pan, Yao; Smith, Stephen C; Sulaiman, Munshi (Wiley Online Library, 2022)
This article was published in The American Journal of Agricultural Economics [©2018 Agricultural and Applied Economics Association] and the definite version is available at: https://doi.org/10.1093/ajae/aay012 The Article's website is at: https://onlinelibrary.wiley.com/doi/10.1093/ajae/aay012